1963
DOI: 10.1007/bf02822475
|View full text |Cite
|
Sign up to set email alerts
|

Methanesulfonic acid catalyzed additions to oleic acid and cyclohexene. III. Addition of acids and substituted phenols

Abstract: Benzoic acid adds to oleic acid in methanesulfonic acid as catalyst‐solvent to form an addition product in 30% yield. Saponification studies on the product reveal that the addition is made via the carboxyl group and no rearrangement of the initial product takes place. A number of substituted benzoic acids were also tried but the yield of addition product was nil. Data are included for the experiments with a number of phenols not previously reported. These include: o‐chlorophenol,2,6‐di‐tert.‐butylphenol, 2,4,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The following aryl ethers from Table 1 have been reported in the literature: Entry 1, 12 Entry 4, 13 Entry 5, 14 Entry 6, 15 and Entry 7. 16 Characterization data for new compounds are given below.…”
Section: Methodsmentioning
confidence: 99%
“…The following aryl ethers from Table 1 have been reported in the literature: Entry 1, 12 Entry 4, 13 Entry 5, 14 Entry 6, 15 and Entry 7. 16 Characterization data for new compounds are given below.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of aromatic compounds to oleic acid has been studied using various types of Lewis and Bronsted acids as catalysts (1,2). Eisner et al (3)(4)(5) reported that methanesulfonic acid was the preferred acid catalyst for the addition reaction of aromatic compounds to oleic acid because this acid gave not only good yields of addition products, but products with less color. Recently, Nakano et al (6) identified all of the reaction products formed when aromatic compounds are reacted with oleic acid in the presence of methanesulfonic acid and proposed a reaction pathway to account for the products identified.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1960, Mangio (1)came to some useful conclusions on the presence of animal and other vegetable fats in olive oil. The application of reversed-phase thin layer (TLC) and paper chromatography revealed distinct differences in the chromatograms of pure olive oil and of samples adulterated with vegetable oil, which can be used for detecting the presence of low concentrations (10%) of vegetable oils in olive oil (2,3,4). Galanos et al (5,6) have shown that differences in the triglyceride composition of vegetable oils can be used for detecting adulteration of olive oil.…”
Section: Introductionmentioning
confidence: 99%